Ultrasound assessment of the hamstrings complex of athletes with MRI correlation. Issue 5 (May 2022) - Fee, C.; Sergot, L.; Kho, J.; Chakraverty, J.
Abstract : Due to anatomical complexity, ultrasound examination of the hamstring muscles is challenging, resulting in potential diagnostic uncertainty and under-confidence in the technique. This leads to a subsequent tendency to favour magnetic resonance imaging (MRI) evaluation, which can delay diagnosis and potential intervention. This article describes a comprehensive technique of ultrasound evaluation of the hamstrings complex, using key anatomical landmarks. A direct comparison of the sonographic landmarks with corresponding MRI appearances is also provided. If these landmarks can be identified successfully, the complex anatomy can be unlocked, thus improving the time and sensitivity of diagnosis of acute injuries, as well as providing a reliable framework for monitoring injury progress and helping to identify candidates for potential intervention. Many of the anatomical landmarks discussed are common areas of injury in elite athletes, encountered frequently in clinical practice.